Image Processing by Using Different Types of Discrete Wavelet Transform - Thakral, Shaveta; Manhas, Pratima (Advanced Informatics for Computing Research, 2019)
Image processing is emerging research area which seeks attention in biomedical field. There are lots of image processing techniques which are not only useful in extracting useful information for analysis purpose but also saves computation time and memory space. Transformation is one such type of image processing technique. Examples of transform techniques are Hilbert transform, Fourier transform, Radon Transform, wavelet transform etc. Transform technique may be chosen based on its advantages, disadvantages and applications. The wavelet transform is a technique which assimilates the time and frequency domains and precisely popular as time-frequency representation of a non stationary signal. In this paper different types of Discrete wavelet transform is applied on an image. Comparative analysis of different wavelets such as Haar, Daubechies and symlet 2 is applied on image and different filters respond are plotted using MATLAB 15.